(untitled) (International Association of Biologicals and Computational Digest, 2023)
Climate change has an impact on forest growth and production both directly and indirectly through changes in temperature, precipitation, weather, and other variables. Also, increased carbon dioxide has an impact on plant development. Urban forests are affected according to how climate change affects water cycles. Cities can more effectively adapt to the impact of climate change on temperature patterns and weather occurrences due to urban trees. Compared to their surroundings, cities are often warmer. Transitions in temperatures and weather patterns over a long period of time are referred to as climate change. Urban forests are more prone to experience climate change effects like temperature increases in urban areas. Urban trees and the numerous advantages they provide to city dwellers are at risk due to climate change. Generally, trees that are more tolerant of drought, have evergreen leaves, and are younger tend to grow bigger and quicker than anticipated, whereas trees that are less tolerant of drought, have deciduous leaves, and are older are more likely to show size restrictions.